1997
DOI: 10.1002/j.1939-4640.1997.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature Capacitation of Bovine Spermatozoa Is Initiated by Cryopreservation

NATHALY CORMIER,
MARC‐ANDRé SIRARD,
JANICE L. BAILEY

Abstract: Poor motility and abnormal acrosomal morphology only partially explain the reduced fertility of cryopreserved bovine spermatozoa. To test the hypothesis that cryopreservation procedures (dilution, cooling, freeze‐thaw) induce capacitation in bovine spermatozoa, two experiments were conducted using semen diluted in egg yolk—Tris—glycerol extender (EYTG) (Tris, tris(hydroxymethyl)aminomethane). Capacitation was determined prior to and following incubation with various concentrations of heparin using the chlortet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Zhang et al [3] demonstrated significant correlations among in vitro semen tests (total sperm concentration and motile sperm concentration), zona pellucidabinding assay, and in vitro blastocyst production. The integrity of the plasma membrane reflects sperm viability and cryopreservation damages this membrane [4][5][6][7][8]. The damage includes swelling and disruption of plasma and acrosome membranes, changes in fluidity [9][10][11], altered influx of calcium [12,13], and changes in enzyme activity [8,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [3] demonstrated significant correlations among in vitro semen tests (total sperm concentration and motile sperm concentration), zona pellucidabinding assay, and in vitro blastocyst production. The integrity of the plasma membrane reflects sperm viability and cryopreservation damages this membrane [4][5][6][7][8]. The damage includes swelling and disruption of plasma and acrosome membranes, changes in fluidity [9][10][11], altered influx of calcium [12,13], and changes in enzyme activity [8,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, capacitation, acrosome reaction, and binding of spermatozoa to the oocyte surface require a biochemically active membrane [14,17,18]. Destabilization of sperm membranes following cooling resembles that of the physiological sperm capacitation [4,12,19]. Considering that capacitated and/or acrosome-reacted spermatozoa have a limited life span [20], this would result in impaired fertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pattern of FT semen was more alike the pattern of fresh sperm cells incubated over time at a physiological temperature. This could be caused by changes in motility complying to capacitation, as it is well known that cryopreservation leads to changes in sperm cells that resembles capacitation [ 25 , 26 ]. Moreover, one could speculate whether fresh sperm cells might have the same changes due to stress induced during incubation at body temperature.…”
Section: Discussionmentioning
confidence: 99%